IoT Monitoring Solution for a Middle-Scale Grid Powered by PV Solar Tracker - Francisco Javier Folgado; Isaías González; Manuel Calderón; David Calderón; Antonio José Calderón (Engineering Proceedings)
The scarcity of fossil fuels and the increase in energy demand, which is growing year after year, have led to the rapid development of technologies and systems for harnessing renewable energy sources (RES). Among these, photovoltaic (PV) energy and its associated technologies stand out for their adaptability and versatility, highlighting among the rest for being one of the most efficient methods for harnessing energy from RES. Beyond the generation processes, the problems derived from the management and monitoring of these systems are outlined. This paper develops the design and implementation of a system based on Internet of Things (IoT) applications for a medium-scale power grid located within the university campus of Badajoz, Extremadura. This grid is partially powered by PV energy by means of a set of 56 panels, with a total power of 60 kW, installed on a solar tracker. The system presented develops the functions of acquisition, management, and monitoring of data from the solar tracker, the transformation center, and the consumption derived from the activities carried out at the School of Industrial Engineering, whose electricity supply comes from the two previous sources. The elements involved in the physical installation are described, as well as the sensors responsible for data acquisition. Regarding the software, the IoT programs used for the development of the system are presented, as well as their intercommunication and handling. Finally, the proposed system is shown under real operation conditions.